Texture and Microstructure of Thermally-Treated Acid-Leached Kaolinitic Clays - Mervat Hassan; Hassan El-Shall (Adsorption Science & Technology)
Natural and modified kaolinitic clays were investigated by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM and EDS) and N 2 adsorption techniques. Disordered, poorly crystalline kaolinite, containing some quartz and very little mica, was calcined at different temperatures and different times and then leached with 25 wt% sulphuric acid for 1 h at 98 °C. Calcination led to a reduction in both the specific surface area and the total pore volume due to dehydroxylation of kaolinite to meta-kaolinite (MK). However, subsequent leaching of the meta-kaolinite had a striking effect on the microporosity of the modified products. Thus, heating at 886 °C at 2 h (to yield MK 2 886°C) and subsequent leaching for 1 h produced porous silica with a specific surface area of 233 m 2 /g and a total pore volume of 0.22 m 2 /g. The increase in the specific surface area (S BET ) of the porous silica was due to the formation of micropores of 1.2–1.8 nm diameter and mesopores of 4.0–5.5 nm diameter inside the porous structure. The variation in the specific surface area and the porosity of acid-leached meta-kaolinite was found to depend not only on the calcination temperatures but also on the calcination time. Increasing the calcination time up to 6 h had a negative effect on the microporosity, attributed to a condensation reaction. The characteristics of the hysteresis loops in the corresponding adsorption/desorption isotherms indicated the formation of mainly slit-shaped pores. A broad band at 2θ = 21.8° in the XRD patterns of the modified samples was assigned to amorphous silica. The infrared spectra of acid-leached meta-kaolinite showed bands at 1095 cm −1 and 795–802 cm −1 , respectively, which could be assigned to a three-dimensional amorphous silica phase.